Going phygital a user-centric Balintawak Marketplace through a converged physical and digital shopping environment - Mesina, Claudette Anne L.
Public markets have been the go-to shopping places due to their accessibility to the general public. In the Philippines, one of the well-known primary markets is the Balintawak marketplace which serves as an important link in the food supply chain between Metro Manila and other agricultural provinces. Currently, it experiences physical and spatial issues that affect its shopping environment and the experience of its users and is affected by the changing shopping trends; thus, it needs to adapt to keep up with the consumer behavior and preferences. With this, the study uses a phygital design approach, which combines physical and digital shopping spaces, to enhance the marketplace and address its physical and spatial issues as it adapts to shopping trends. Surveys, focus group discussions, and interviews were conducted to gather data on the marketplace problems, user satisfaction, preferences, and perceptions on shopping environment and phygital design. Findings show that the users have neutral satisfaction with the marketplace's shopping environment and prefer user-friendly technology for convenient shopping. With this, the proposed design has key areas like the e-market zone, activity area, cash-in and cash-out stations, and pick-up points which provide efficient, experiential, and engaging phygital services such as simultaneous online and offline shopping, contactless payments, and click-and-collect. Holistically, the phygital design for Balintawak marketplace makes it user-centric as it addresses the problems and preferences of use and enhance its identity and function as a public space that holds economic and socio-cultural significance in the city.